Peran Brand Attitude dalam Memediasi Inovasi Produk dan Celebrity Endorser terhadap Minat Beli (Studi pada Produk Bedak Padat Kosmetik Pixy di Kota Cilegon) - Afriani Fitriyah; Sutisna Sutisna; Umalihayati Umalihayati (Ekonomis: Journal of Economics and Business, 2024)
This research aims to explore the influence of product innovation and the use of celebrity endorsers on purchase intention with special attention to the role of brand attitude as an intervening variable. The research applies a quantitative approach and uses a purposive sampling method. The survey used a Google form with 400 female respondents aged 20-34 years in Cilegon City. The analysis method uses descriptive and inferential statistics, data processing uses SmartPLS software. The results of this research show that a significant influence was found between the product innovation variable and the celebrity endorser variable on the brand attitude variable. Furthermore, a significant influence was also found between the celebrity endorser variable and the brand attitude variable on the purchase interest variable, but no influence was found between the product innovation variable on the purchase interest variable for Pixy Cosmetics pressed powder products in Cilegon City. The brand attitude variable can be used as a mediating variable for the influence of the product innovation variable and the celebrity endorser variable on purchasing interest in Pixy Cosmetics pressed powder products in Cilegon City.